Human papillomavirus-independent cervical cancer. Issue 1 (1st November 2021) - Fernandes, Andreina; Viveros-Carreño, David; Hoegl, Jorge; Ávila, Maira; Pareja, Rene
Abstract : Cervical cancer is the fourth most frequent cancer in women worldwide, representing nearly 8% of all female cancer deaths every year. The majority of cases of cervical cancer are caused by human papillomavirus (HPV); however, up to 5% of tumors are not associated with HPV-persistent infection and, moreover, the new WHO Female Genital Tumors classification subdivided cervical squamous and adenocarcinomas into HPV-associated and HPV-independent tumors. Based on this new information, the aim of this review is to provide an overview of HPV-independent cervical cancer, evaluating diagnostic techniques, molecular profiles, and clinical outcomes. The HPV-independent tumors are characterized by a differentiated molecular profile with lower proliferative activity, a p53 immunostaining, a decreased expression of cyclin-dependent kinase inhibitor proteins, such as p16, p14, and p27, and alterations in PTEN, p53, KRAS, CTNNB1, ARID1A, and ARID5B . HPV-independent tumors are associated with both adenocarcinomas and squamous histologic subtypes, with lymph node involvement in the early stages, more distant metastasis, and generally worse oncological outcomes. Thus far, no specific therapeutic strategies have been developed based on HPV status; however, with advancing knowledge of differences in the molecular profiles and possible targetable alterations, novel approaches may offer potential options in the near future. Investigators should report on clinical outcomes, evaluating the overall response rates to specific treatments, and consider new biomarkers to establish more accurate prognostics factors.